AC flashover characteristics and arc development process of glaze ice-covered insulators in natural environment. (February 2022) - Zong, Chunyu; Hu, Yuyao; Jiang, Xingliang; Xian, Richang; Liu, Zongyuan; Sun, Jianliang
Highlights: The mechanism of icicle growth on the energized insulator is revealed. Flashover voltage of iced insulators in the lab is lower than that in the field. Arc extinction-reignition and floating phenomena are significant in the field. Abstract: Ice accretion on the insulators can reduces the creepage distance to a certain extent as low as the dry arc distance, which may cause flashover trip and subsequent blackout. Extensive research on insulator icing has been carried out in a controlled-climate room. Due to great differences in environmental parameters between laboratory simulation and field tests, icing characteristics and discharge development of ice-covered insulator obtained in the laboratory cannot veritably reflect natural icing law and arc propagation process. Consequently, in the present study the glaze-icing on energized insulators was investigated on site, and the mechanism of icicle growth on the insulator energized with different voltage levels was revealed. Meanwhile, AC flashover performances and arc discharge development of ice-coated insulators for the two test conditions were compared and discussed. Results show that for a weak electric field, icicle firstly grows vertically, and then bends to the axis of the insulator when its length reaches to a certain level. Nevertheless, icicle develops towards the axis at the beginning under a high electric field. AC flashover voltage of ice-accreted insulators increases exponentially with an increasing applied voltage, while the relation of flashover voltage and ice weight fits well with a negative power function. Icing flashover voltage of the insulators obtained in natural environment is 14%～21% higher than that in the chamber. Compared with the flashover in the laboratory, during the discharge of the insulators naturally covered with ice, arc extinction-reignition and floating phenomena are more significant, and the ice-melting is more severe.